HnRNP-L-regulated circCSPP1/miR-520h/EGR1 axis modulates autophagy and promotes progression in prostate cancer - Jianming Lu; Chuanfan Zhong; Junqi Luo; Fangpeng Shu; Daojun Lv; Zezhen Liu; Xiao Tan; Shuo Wang; Kaihui Wu; Taowei Yang; Weibo Zhong; Bin Wang; et al. (Elsevier, 2021)
The circRNAs, a new subclass of non-coding RNAs that are catalyzed by RNA-binding proteins (RBPs), have been reported to be associated with the progression of multiple types of cancer. We previously discovered that heterogeneous nuclear ribonucleoprotein L (HnRNP-L), a multi-functional RBP, is associated with pro-proliferation and anti-apoptosis activities in prostate tumor cells. In this study, we aim to establish the biological relevance of circCSPP1 (a newly discovered signature circRNA in prostate cancer [PCa]) and HnRNP-L to prostate cancer progression. First, we demonstrated that circCSPP1 expression was higher in prostate cancer tissues than in benign tissues and higher in prostate cancer cells than in benign cells. Then, the in vitro gain- and loss-of-function experiments showed that the circCSPP1 expression in prostate cancer cells was regulated by HnRNP-L, and the increased circCSPP1 significantly induced autophagy, which led to an enhanced potential in proliferation, migration, and invasion of prostate cancer cells. These results were consistent with the in vivo experiment where increased or decreased circCSPP1 was associated with higher or slower growth rate in grafted tumors. Finally, we demonstrated the potential competing endogenous RNA network, involving circCSPP1, miR-520h, and early growth response factor 1 (EGR1), in prostate cancer cells, which may play an important role in prostate cancer progression. Our study indicated that the increase in circCSPP1 in prostate cancer, which may be catalyzed by HnRNP-L, can induce cellular autophagy through the circCSPP1-miR-520h-EGR1 axis, leading to the progression of prostate tumor. This newly discovered circRNA biomarker may be used for clinical prognosis of prostate cancer as well as for development of novel therapy plans.